2017
DOI: 10.2147/ndt.s126678
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of localized connectivity in schizophrenia patients and their unaffected relatives: a meta-analysis of resting-state functional magnetic resonance imaging studies

Abstract: ObjectiveThe localized dysfunction of specialized brain regions in schizophrenia patients and their unaffected relatives has been identified in a large-scale brain network; however, evidence is inconsistent. We aimed to identify abnormalities in the localized connectivity in schizophrenia patients and their relatives by conducting a meta-analysis of regional homogeneity (ReHo) studies.MethodsFourteen studies on resting-state functional magnetic resonance imaging, with 316 schizophrenia patients, 342 healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 53 publications
(56 reference statements)
0
36
0
Order By: Relevance
“…Our study found increased ReHo values in right SFG. A meta-analysis also showed increased ReHo values in the SFG in both patients with first-episode schizophrenia and with treated schizophrenia [13]. The SFG is a significant component of the DLPFC [61].…”
Section: Discussionmentioning
confidence: 91%
“…Our study found increased ReHo values in right SFG. A meta-analysis also showed increased ReHo values in the SFG in both patients with first-episode schizophrenia and with treated schizophrenia [13]. The SFG is a significant component of the DLPFC [61].…”
Section: Discussionmentioning
confidence: 91%
“…This data set is available at a previous study [7] and contains raw anatomical and functional MR data from patients with Schizophrenia and healthy controls, ranging in age from 18 to 65 years old. Resting fMRI, anatomical MRI, phenotype data for every participant including gender, age, handedness and diagnostic information are released.…”
Section: Data Source and Availabilitymentioning
confidence: 99%
“…Also, schizophrenia is associated with volume deficits in PreCG [5] . Another research indicates the patients with schizophrenia showed lower activation in left PreCG than right PreCG [6] and a regional homogeneity (ReHo) study showed decreased ReHo in right precentral gyrus [7] . In this research, we examined the PreCG functional connectivity impairment in patients with schizophrenia using ROI based analysis [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Also, SCH is associated with volume deficits in Precentral gyrus [15]. Another research indicates that the patients with SCH showed lower activation in left PreCG than right PreCG [10] and a regional homogeneity (ReHo) study showed decreased ReHo in right Precentral gyrus [19].…”
Section: Introductionmentioning
confidence: 98%